How can frontline managers' creativity in the hospitality industry be enhanced? Evidence from an emerging country. (September 2021) - Dang, Van Thac; Lisovich, Mai Nguyen; Vo-Thanh, Tan; Wang, Jianming; Nguyen, Ninh
Abstract: On the basis of social cognitive theory, social interaction theory, and cognitive flexibility theory, this study investigates the relationship between workplace learning and frontline managers' creativity in the hospitality industry, with the mediating roles of knowledge sharing and cognitive flexibility. This study uses structural equation modeling to test hypotheses using a three-wave time-lagged sample data of 307 frontline managers in the hospitality industry in Vietnam. Results show that workplace learning is positively related to frontline managers' creativity. Furthermore, knowledge sharing has a positive mediating effect in the relationship between workplace learning and frontline managers' creativity. In addition, cognitive flexibility positively mediates the relationship between workplace learning and frontline managers' creativity. Cognitive flexibility also positively mediates the relationship between knowledge sharing and frontline managers' creativity. These findings provide implications for both academics and practitioners in the hospitality industry regarding enhancing frontline managers' creativity through workplace learning, knowledge sharing, and cognitive flexibility.